Highly porous alumina cellular ceramics bonded by in-situ formed mullite prepared by gelation-assisted Al2O3–Si particle-stabilized foams. Issue 8 (1st June 2020) - Liu, Jingjing; Ren, Bo; Rong, Yedong; Zhao, Yi; Wang, Lu; Lu, Yuju; Wang, Chao; Sang, Guolong; Yang, Jinlong
Abstract: Engineering high performance cellular ceramics with both ultralow density and satisfactory compressive strength for practical applications still represents a grand challenge. Herein, alumina-based cellular ceramics bonded by in-situ formed mullite phase were constructed by Al2 O3 –Si-boehmite particle-stabilized foams. The gelation of boehmite sol improved the stability and harnessed the deformation of dried Al2 O3 –Si composite foam. The oxidation of silicon and further generation of in-situ mullite phase enhanced the chemical bond between alumina particles on cell walls, resulting in the superior mechanical properties. As an exemplar, the resulting cellular ceramic possessed the robust compressive strength of 2.26 MPa at a high porosity of 87.8%. The gelation-assisted Al2 O3 –Si particle-stabilized foams provide a facile and convenient strategy for construction of composite ceramic foams with high porosity and robust strength.